Cobertura del suelo del año 2016 del cantón Tarrazú, San José, Costa Rica - Fallas-Ureña, Manfret Josue (Instituto Tecnológico de Costa Rica, 2016)
The study consisted in the classification of the soil cover of the canton of Tarrazú. Three LANDSAT 8 images were used, which were used together to make the final classification, the classification was validated, the final map of the classification for the Tarrazú canton was elaborated and for the San Marcos, San Lorenzo districts And San Carlos. At the Tarrazú canton level the coverage with the largest area was the secondary forest, which covered 31.5% (9414.9 ha) of the canton. Mature forest, secondary forest, pasture and perennial (coffee) cultivation had a greater presence in the district of San Lorenzo. The general accuracy of the classification reached a value of 86.86% taking into account the five classes analyzed with the error matrix. The results obtained were transmitted in a workshop to the officials of the Municipality of Tarrazú, explaining their correct use, which generated a list of possible actions in the canton of Tarrazú related to the land cover.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2016.
Keywords: Cobertura forestal; Clasificación de suelos; Bosque; Café; Ingeniería forestal; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Forestry